La utilización de software de código libre en el área de biblioteconomía y documentación en España: el caso de la Universidad Complutense de Madrid - Martínez-comeche, Juan Antonio; Ramos Simón, Luis Fernando; Razquin Zazpe, Pedro; Tejada Artigas, Carlos (Revista General de Información y Documentación, 2007)
Analysis of a survey passed to the teaching staff of the University School of Library and Information Science of the Complutense University with the purpose of knowing its opinion and attitude towards the open source software like a possible solution for its use like didactic material, facilitating therefore the process of European convergence with respect to the degree in Information and Documentation. The teaching staff of the EUBD is conscious of the advantages of the open source software and are pronounced mainly favourable to the use of such programs, being the ignorance of his existence the main culprit of his lack of use on the part of the educational professionals.